Feto-maternal Outcome in Pregnancies Complicated by Hypertensive Disorder: A Retrospective Study at a Tertiary Care Centre of Eastern Nepal - Karki, Gyanendra Man Singh; Priyadarshini, Mona; Pradhan, Tarun (Birat Journal of Health Sciences, 2020)
Introduction: Hypertensive disorder of pregnancy is one of the major cause of maternal and fetal morbidity and mortality. Objective: The objective of this study was to estimate the associated maternal and fetal outcome and complications in pregnancies complicated by hypertensive disorders at a tertiary care hospital in eastern Nepal. Methodology: This retrospective cross section observational study included purposely-selected one hundred thirty four pregnant women from April 2019 to April 2020 in the Department of Obstetrics and Gynaecology at Birat Medical College Teaching Hospital, Tankisinuwari, Morang, Nepal. Maternal age, gravidity, period of gestation at presentation, associated maternal comorbidities/ risk factors, mode of delivery, indication for surgery, maternal outcome and complications, fetal outcome was recorded and data was analysed using SPSS version 23 software. Result: Out of the 134 study population,35.8% of the mothers with hypertensive disorders were noted in the age group between 25-29 years and almost two third of the patients were multigravida. 55.2% patients had mild, while 44.8% had severe hypertension. About 83.6% of the hypertensive pregnant mothers delivered preterm between 33 to 36 weeks of gestation. 61.9% mothers underwent cesarean section with the most common indication being non-reassuring fatal heart rate pattern, while 34.3% women delivered vaginally. 86 out of 134 cases did not develop any complications while, postpartum haemorrhage was the most frequently encountered complication seen in 17.9% cases followed by eclampsia encountered in 13.4% patients. The mortality encountered was 0.7%. Neonatal complications were found in 50% cases, 15.7% neonates had low APGAR score and 8.2% had meconium aspiration, while 4.5% intrauterine deaths and 3% neonatal deaths were observed. Conclusion: There is adverse impact of hypertension during pregnancy over maternal and perinatal outcome. Hence, early identification and prompt referral to the well-equipped center is necessary to reduce the associated morbidity and mortality.